THE FUTURE OF THE ARABIC LANGUAGE IN SOCIAL MEDIA - Sheraz Bal'abriyya, (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
Today, in light of technological and digital developments, the Arabic language faces a number of difficult challenges, especially on social media, given the radical transformations these sites bring about in the patterns of linguistic communication in the Arab world, which leads to the hybridization of the Arabic language and a decline in its status compared to foreign languages.